New tendencies in non-surgical periodontal therapy - Alex Nogueira HAAS; Flavia FURLANETO; Eduardo José GAIO; Sabrina Carvalho GOMES; Daniela Bazan PALIOTO; Rogerio Moraes CASTILHO; Mariano SANZ; Michel Reis MESSORA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this review was to update the evidence of new approaches to non-surgical therapy (NSPT) in the treatment of periodontitis. Preclinical and clinical studies addressing the benefits of adjunctive antimicrobial photodynamic therapy, probiotics, prebiotics/synbiotics, statins, pro-resolving mediators, omega-6 and -3, ozone, and epigenetic therapy were scrutinized and discussed. Currently, the outcomes of these nine new approaches, when compared with subgingival debridement alone, did not demonstrate a significant added clinical benefit. However, some of these new alternative interventions may have the potential to improve the outcomes of NSPT alone. Future evidence based on randomized controlled clinical trials would help clinicians and patients in the selection of different adjunctive therapies.